Manyŏ . 2 = The witch. 2, The other one [videorecording (DVD)] - Pak, Hun-jŏng; Pak, Hun-jŏng; Sin, Si-a, 1998-; Pak, Ŭn-bin, 1992-; Chin, Ku, 1980- (Well Go USA Entertainment, 2022)
Sequel to the popular Korean action-thriller The Witch: Subversion: After a mysterious girl emerges as the sole survivor of a bloody raid on the research facility behind the top-secret Witch Program, she is rescued by a couple who understands the grave danger the girl now faces. However, as the assassins tasked with locating and silencing the girl move ever closer, the lives of all three fall under increasingly great peril.